2006
DOI: 10.1149/1.2357195
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Contacts to p-Type III-V Semiconductors for the Base of Heterojunction Bipolar Transistors

Abstract: Ohmic contacts to p-type In0.25Ga0.75Sb, InAs, and InAs0.8P0.2 have been investigated for the base of heterojunction bipolar transistors. On all these semiconductors, using Pd and/or Pt as the first layer in the metallization stack provided the lowest contact resistances. Specific contact resistances as low as 3 x 10-7 Ω-cm2 were measured for Au/W/Pd/p-InGaSb. Thin reactive layers of Pd or Pt were used beneath an unreactive W barrier to keep the contacts shallow, but contact resistance and thermal stability we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The contact resistance values for metallization schemes in Sb-containing InAs-based semiconductors have been limitedly reported. For instance, Mohney and co-workers presented an extended study on distinct three- and four-layered ohmic contact metallization with Au cap layer to maintain a low metal sheet resistance to highly Be-doped InAs (>10 19 cm −3 ) with ρ c at a level of 10 −6 Ω·cm 2 [ 17 , 18 ]. Guo et al conducted an analysis on highly Be-doped InAs/InAsSb cap structure, yielding an ultralow ohmic contact with ρ c of 1.3 × 10 −8 Ω·cm 2 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The contact resistance values for metallization schemes in Sb-containing InAs-based semiconductors have been limitedly reported. For instance, Mohney and co-workers presented an extended study on distinct three- and four-layered ohmic contact metallization with Au cap layer to maintain a low metal sheet resistance to highly Be-doped InAs (>10 19 cm −3 ) with ρ c at a level of 10 −6 Ω·cm 2 [ 17 , 18 ]. Guo et al conducted an analysis on highly Be-doped InAs/InAsSb cap structure, yielding an ultralow ohmic contact with ρ c of 1.3 × 10 −8 Ω·cm 2 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The thermal stability studies conducted by Lee et al [16] on InAs/graded InGaAs structure revealed that the In atoms diffuse and penetrate into the 110 nm thick Ti layer, leading to InAs film decomposition at 350 • C. Other more complex Au-containing metallization schemes were tested as well on InAs-based structures using distinct adhesive/barrier layers such as Pd, Co, Ni, etc. [17][18][19]. Nevertheless, Au is normally the main constituent of metallization schemes due to high electrical conductivity and excellent corrosion resistance [20] and is vital in processing semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation